PENGARUH EQUITY MULTIFLIER DAN RETURN ON TOTAL ASSETS TERHADAP RETURN ON EQUITY (STUDY KASUS PADA BUMN SEKTOR KONSTRUKSI PERIODE 2012-2016) - Umar Hamdan Nasution (Bisnis-Net, 2018)
The purpose of this case study is to analyze the effect of equity multiplier and return on total assetsto return on equity. The variables studied were equity multiplier, return on total and return on equity.The research method used is descriptive analysis using multiple linear regression analysis as a toolof analysis. The population and samples used in the data used in this case study are state-ownedconstruction sector 2012-2016 with census method. The result of the partial regression analysisshows that the equity multiplier and return on total assets have a positive and significant effect onreturn on equity. Then, from the regression analysis simultaneously shows that the equity multiplierand return on the total assets have a positive and significant effect on return on equity.